Optimalisasi Rencana Anggaran Biaya pada Perumahan Central Raya Tiban Menggunakan Perhitungan SNI dan Kontraktor - Delvina Luo; Jody Martin Ginting; Amanatullah Savitri (Jurnal Manajemen Teknologi & Teknik Sipil, 2022)
In the construction project, construction management is needed in order to get results that are in accordance with the objectives of the development. One of the elements of project management is cost management. Poor cost management can lead to cost overruns or over budgets to the detriment of project owners and contractors. One of the methods that can be used in preparing the project cost budget is the SNI calculation and the contractor's calculation. The purpose of this study was to determine the comparison of the budget plan using the SNI method and the contractor's calculation. The research was conducted by collecting data on the Central Raya Tiban housing development project. Furthermore, an analysis using the SNI and contractor is carried out and compares the results of the calculations of the two methods. The results of the study obtained that the estimated cost budget plan from the calculation of the contractor was Rp. 283,827,332, while the results with the SNI were Rp. 330,333,371. From these data, it can be seen that the contractor's calculation is more optimal when compared to the calculation of SNI with a difference of Rp. 46,506,039 or 14.08% of the total value of the estimated cost budget based on the SNI calculation method. This can be used as a reference in preparing a cost budget in order to reduce development or project costs so that they become optimal and in accordance with the wishes of the project owner.